Disentangling different moisture transport pathways over the eastern subtropical North Atlantic using multi-platform isotope observations and high-resolution numerical modelling - Dahinden, Fabienne; Aemisegger, Franziska; Wernli, Heini; Schneider, Matthias; Diekmann, Christopher J.; Ertl, Benjamin; Knippertz, Peter; Werner, Martin; Pfahl, Stephan (European Geosciences Union, 2021)
Due to its dryness, the subtropical free troposphere plays a critical role in the radiative balance of the Earth’s climate system. But the complex interactions of the dynamical and physical processes controlling the variability in the moisture budget of this sensitive region of the subtropical atmosphere are still not fully understood. Stable water isotopes can provide important information about several of the latter processes, namely subsidence drying, turbulent mixing, dry and moist convective moistening. In this study, we use high-resolution simulations of the isotope-enabled version of the regional weather and climate prediction model of the Consortium for Small-Scale Modelling (COSMO$_{iso}$) to investigate predominant moisture transport pathways in the Canary Islands region in the eastern subtropical North Atlantic. Comparison of the simulated isotope signals with multi-platform isotope observations (aircraft-based in situ measurements, ground-based and space-based remote sensing observations) from a field campaign in summer 2013 shows that COSMO$_{iso}$ can reproduce the observed variability of stable water vapour isotopes on time scales of hours to days, and thus allows studying the mechanisms that control the subtropical free-tropospheric humidity. Changes of isotopic signals along backward trajectories from the Canary Islands region reveal the physical processes behind the short-term isotope variability. We identify four predominant moisture transport pathways of mid-tropospheric air, each with distinct isotopic signatures: (1) Air parcels originating from the convective boundary layer of the Saharan heat low (SHL). These are characterised by a homogenous isotopic composition with a particularly high δD (median mid-tropospheric δD = −122 ‰), which results from dry convective mixing of low-level moisture of diverse origin advected into the SHL. (2) Air parcels originating from the free troposphere above the SHL. Although experiencing the largest changes in humidity and δD during their subsidence over ...